NILAI SOSIAL DALAM TRADISI MAKAN BAJAMBAU PADA PERAYAAN PENYANTUNAN ANAK YATIM PIATU DUSUN JAWI-JAWI DAN DUSUN PADANG TENGAH - Yulna Pilpa Sari; Hasnah Faizah; Auzar Auzar (Jurnal Ilmu Budaya, 2023)
Makan Bajambau is one of the traditions which is still preserved by the people in Jawi-Jawi village and Padang Tengah village. It is a tradition in which the people eat together in one decided place by using small plates. The biggest tradition held by the Jawi-Jawi and Padang Tengah villages is in the moment of sponsoring orphans. Makan Bajambau is one of the elements in this occasion which is a must. This tradition is conducted every year and villagers participate in vibrant. Makan Bajambau is not just eating together but contains valuable togetherness and brotherhood values. Thus these writings aim to describe the social values in this tradition. The method used is ethnography and data collection uses observation, interviews, and documentation. The results show some social values in the Makan Bajambau tradition among others. The affection, togetherness, and brotherhood. Triggered by the good values of the Makan Bajambau ritual in sponsoring the orphans in Jawi-Jawi and Padang Tengah villages, the villagers preserve this tradition and pass it down to the next generation.